O Curso de Licenciatura em Ciências Biológicas da Universidade Regional Do Cariri – URCA: constituição, desenvolvimento curricular e formação docente (1987 – 2017) - Torres, Cícero Magérbio Gomes (2017)
The history of curriculum, as an integral part of the History of Education, exemplifies the processes of change experienced by the curriculum, mobilized by social, historical and cultural artifacts, articulated with those who attend educational institutions with a view to a social epistemology of knowledge and its determinants, social and political, on knowledge and its effects. In this context, the interest in research on the Biological Sciences course of the Regional University of Cariri - URCA emerges. Studying the field of curriculum and the training of the science teachers in this course and relating it to historical issues (1987-1999), economic, social and cultural policies, mark the challenges of building this thesis. Hence, the general objective is to understand the historical constitution process of the Regional University of Cariri - URCA, identifying its political, social, economic, cultural, pedagogical, didactic and curricular determinants as well as its implications for vocational training Teacher of Basic Education. Oral History was used as methodology, structured in qualitative, descriptive and analytical research. The place of realization of the research is the Biological Sciences Course of the Regional University of Cariri - URCA. Five retired teachers who participated in the course implementation and development process participated in the study. The documentary corpus consisted of oral and documentary sources and the technique of data collection was given through the recorded interview and in the systematization of the documentary information in a field diary. The data were analyzed using NVIVO software version 10.0. In this perspective, oral (textualized) statements from the interviews were organized into categories: Higher Education, Catarsis, Science and Reminiscences and in the subcategories: Higher Education of Cariri, History of Curriculum, Power and Scientific, Technological and Formative Development, respectively. The data analyzed reveal that the course has undergone successive modifications in its pedagogical projects while at the same time it explicitly contradicts its curricular organization, due in large part to the political, economic, social and legal determinants present in society.